2005
DOI: 10.1108/09513550510591515
|View full text |Cite
|
Sign up to set email alerts
|

UK leisure centres under best value: a strategic analysis

Abstract: Purpose - To understand the effects of the best value regime on the public provision of recreation at the level of the leisure centre. Design/methodology/approach - A strategic auditing device is applied to 87 leisure centres to investigate the strategic variables of environmental stability and attractiveness, service strengths and financial resources. The analysis produces a typology of leisure centres, and evaluates the prospects of each type under best value. Findings - The findings suggest that a large num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 34 publications
2
17
0
Order By: Relevance
“…For example, Irwin, Zwick, and Sutton's (1999) investigation across 15 professional sport franchises in the USA concentrated more on tactical marketing Á identifying several important tactics rather than practices of a more strategic nature. Moreover, in Britain, the findings of Benson and Henderson's (2005) study of strategic planning in British leisure centres confirmed those of earlier American studies by Boardman and Vining (2000) and Stotlar (2002), namely: that despite articulating a desire for a planned strategic approach, management (mis)perceptions of cost constrained its use. Therefore, within Britain, Australia and New Zealand, the overriding purpose of this research is to investigate both the adoption of strategic marketing practices and their contribution to golf organisation business performance.…”
Section: Introductionsupporting
confidence: 83%
“…For example, Irwin, Zwick, and Sutton's (1999) investigation across 15 professional sport franchises in the USA concentrated more on tactical marketing Á identifying several important tactics rather than practices of a more strategic nature. Moreover, in Britain, the findings of Benson and Henderson's (2005) study of strategic planning in British leisure centres confirmed those of earlier American studies by Boardman and Vining (2000) and Stotlar (2002), namely: that despite articulating a desire for a planned strategic approach, management (mis)perceptions of cost constrained its use. Therefore, within Britain, Australia and New Zealand, the overriding purpose of this research is to investigate both the adoption of strategic marketing practices and their contribution to golf organisation business performance.…”
Section: Introductionsupporting
confidence: 83%
“…One of the major advantages of trust management is a financial advantage, in terms of both reduced VAT and seeking new capital not available to local authorities (Collins 2009). Local authority operators are prevented from accessing a variety of funding sources open to trusts, and they are constrained by the requirement to make efficiency savings of 2% a year, despite attempting to improve the quality of services to their local citizens (Benson and Henderson 2005). However, many of the trusts formed to manage leisure facilities in the UK do not have significant assets to utilize in the acquisition of capital finance.…”
Section: Changes In the Management Of Leisure Facilitiesmentioning
confidence: 95%
“…Neither commercial contractors nor trusts have staff employed by local authorities, but operate as independent organizations. Legislative changes, particularly Compulsory Competitive Tendering in the late 1980s, led to a significant minority of local authorities withdrawing from direct management of sports and leisure centres, in favour of commercial contractors or trusts (Benson andHenderson 2005, Collins 2009). …”
Section: Introductionmentioning
confidence: 98%
“…The SPACE framework has been used in the literature to analyse a range of industries: biotechnology in the UK (Ranchhod & Henderson, 1995); manufacturing in South Africa (Radder & Iouw, 1998); manufacturing in the UK (Li & Hamblin, 2003); professional football in England (Cross & Henderson, 2003) and leisure centres in the UK (Benson & Henderson, 2005a, 2005b.…”
Section: Methodsmentioning
confidence: 99%
“…While the original SPACE framework used Likert scales from 0 to 6, previous research in this area (Benson & Henderson, 2005a, 2005b suggested that respondents are not comfortable with scoring 0 for some questions. It was, therefore, decided to use a scale of 1 -7 throughout.…”
Section: Research Instrument and Distributionmentioning
confidence: 99%